New religious scholarship on Sexuality - Hunt, Mary E. (Mandrágora, 2025)
New religious scholarship on sexuality features changes in both the assumptions that underlie it and the methods used to accomplish it. Religious scholarship in general is woefully behind the secular tide on these matters. The challenge to progressives is twofold: (1) to get up to speed on sexology and related research so as to develop religious positions that are consistent with today's reality; (2) to disseminate our findings and insights through the most effective public means possible rather than engage in old debates among ourselves.